Rumah Makan mKitchen for Free Food Distribution - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Ismail, Amelia Ritahani; Abdul Kadir, Andi Fitriah; et al. (mKitchen, KICT IIUM, 2023)
Rumah Makan mKitchen provides enhancement of knowledge, skill, employment, and entrepreneurship. Rumah denotes a centre for enhancement, employment and entrepreneurship. Makan denotes sourcing, cooking and distribution of quality food. mKitchen denotes Masjid and Masyarakat (or community) Kitchen. JEL Classification: M13 and M15